The Dilemma of Being American as a Consequence of Ethnic Segregation in Toni Morrison's Beloved (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2019)
Slavery was a central institution in American society and was accepted as normal and applauded as a positive thing by many white Americans. America was full of Negro slaves when there were many injustice actions done by white people to black people. Beloved is a novel written by Toni Morrison in 1987, explores the hardships endured by a former slave woman and her family during the slavery and the Reconstructions eras. This study aims to explain the dilemma experienced by the main character of being American and its correlation between the main character’s dilemma and ethnic segregation by the White Americans against the Afro-Americans as portrayed in Beloved novel. The method used in this study is a qualitative study analyzed by deconstruction theory of Paul de Man. Meanwhile, the method of data analysis is based on the dilemma experienced by African-American people in the novel and its correlation between the dilemma and ethnic segregation. Morrison’s novel shows that the dilemma experienced by the main character in the novel is divided into the episodes of control, gender role, and humanity service. The correlation between the dilemma and ethnic segregation is portrayed through the struggle of Afro-American people fight against the domination of White Americans. In conclusion, ethnic segregation in America creates dilemma for Afro-American or black people and it should be removed to vanish any differentiation and live in harmony. Keywords: American, Deconstruction, Dilemma, Ethnic Segregation